A Retrospective: the Impact of Research on Cotton Pest Control in Central Africa and Development of Ultra-Low Volume Spraying for Small Scale Farmers Between 1958–72. (1st February 2014) - Matthews, Graham
While the introduction of ULV spraying provided a very effective means for farmers to protect their cotton and other crops such as cowpea from insect attack industry was supplying insecticides to use in knapsack sprayers, but in areas with poor water supplies farmers could not use the knapsack sprayer, so implementation of ULV needed the supply of suitably formulated insecticides readily available throughout the cotton growing areas. While this was effectively achieved in most of the Francophone West African countries, it was not in other parts of Africa due to other problems, including lack of a guaranteed price for the seed cotton at harvest. This meant that the success of ULV spraying was limited. Other research with another ULV sprayer, the 'Electrodyn' also showed good yields were possible (Matthews, 1990), but after a short period of its use, mainly in Angola and Mozambique, the development of the equipment by the industry ceased. The higher cost of the oil-based ULV formulations and a need to have a range of different insecticides to off-set the problem of resistance to pyrethroids combined with a need for flexibility of choice of insecticide to follow an integrated pest management programme, led to the adoption of VLV spraying. This was possible by the introduction of a new generation of spinning disc sprayer – the ULVA+, which had an improved disc design and lower power consumption (Clayton et al., 1993). Over this period there was also a policy of privatisation which affected the parastatals and the management of the cotton crop, so with a lack of extension services and credit, farmers were unable to follow the recommendations. Some farmers reverted to using knapsack sprayers. Where this occurred yields were undoubtedly affected adversely. The extent to which spraying against bollworms will now decrease depends on when more countries in Africa accept the genetic modification of incorporating genes that express the toxins produced by Bacillus thuringiensis. Apart from South Africa, only Burkina Faso has grown Bt cotton so far. As Bt cotton only protects the crop from lepidopteran pests, there is still a need to grow a variety resistant to jassids, although early season infestations can be controlled by using an insecticide seed treatment. Nevertheless, some sprays may continue to be needed if whiteflies and other pests infest crops. Clearly adoption of the new spinning disc sprayer technology has depended on having the appropriate extension infrastructure to disseminate the recommendations, combined with industry to support distribution of the inputs required, whether the correct seed, agrochemicals or equipment and for marketing of the crop. For this to happen, government needs to provide a policy which will sustain the industry.